The color compendium - Hope, Augustine (Van Nostrand Reinhold, 1990)
Book features an A to Z encyclopedia, cross-referenced for easy access to all information; sections on painting and harmony, illustrating fundamental color techniques of artists; a section of color systems, explaining their development and use; sections on color communication and symbolism; analysis and discussion of color trends and cycles; biographies of leading historical and contemporary color theorists, and commentaries on their ideas; a fully illustrated section of historic and twentieth-century palettes and their source artifacts.